2018
DOI: 10.1080/13668803.2018.1531827
|View full text |Cite
|
Sign up to set email alerts
|

‘I need to be there’: British South Asian men’s experiences of care and caring

Abstract: This article provides an insight into British South Asian men's experiences of care and caring. Care is gendered, however the ways in which care features in the lives of British Asian men is under-researched and demands attention, particularly given the changing demographics in the UK. The discussion draws on qualitative empirical research with a sample of British Asian men in their early thirties to early fifties. In depth interviews were conducted to consider roles and responsibilities within families and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 37 , 38 Similarly, some cultures have contrasting views on the responsibility of family and friends to caregiving 39 and be more likely to live nearby to family members which may facilitate caregiving. 40 Such analyses to explore the relationship between cultural differences and caregiving for pain would be valuable.…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 Similarly, some cultures have contrasting views on the responsibility of family and friends to caregiving 39 and be more likely to live nearby to family members which may facilitate caregiving. 40 Such analyses to explore the relationship between cultural differences and caregiving for pain would be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that SAM are embracing more egalitarian gender role orientations. For example, Gill (2020) found that SAM are increasingly engaged in caregiving responsibilities, suggesting "caring masculinities" are becoming more central to their identity.…”
Section: Social Identities and The Implications Of Fiwmentioning
confidence: 99%